2022
DOI: 10.1038/s42003-022-03823-w
|View full text |Cite
|
Sign up to set email alerts
|

Human lung-resident mucosal-associated invariant T cells are abundant, express antimicrobial proteins, and are cytokine responsive

Abstract: Mucosal-associated Invariant T (MAIT) cells are an innate-like T cell subset that recognize a broad array of microbial pathogens, including respiratory pathogens. Here we investigate the transcriptional profile of MAIT cells localized to the human lung, and postulate that MAIT cells may play a role in maintaining homeostasis at this mucosal barrier. Using the MR1/5-OP-RU tetramer, we identified MAIT cells and non-MAIT CD8+ T cells in lung tissue not suitable for transplant from human donors. We used RNA-sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…is the expression of the NK receptor KLRB1. These findings closely align with previously identified markers associated with human MAIT and Vd2g9 + gd T cells (Davey et al, 2018;Meermeier et al, 2022;Park et al, 2019) 12), is characterized by increased expression of CX3CR1 (Supplementary Figure 13). The graded expression of CX3CR1 correlates with the differentiation of both CD4 and CD8 T cells towards an effector state (Zwijnenburg et al, 2023).…”
Section: Gene Expressionsupporting
confidence: 90%
“…is the expression of the NK receptor KLRB1. These findings closely align with previously identified markers associated with human MAIT and Vd2g9 + gd T cells (Davey et al, 2018;Meermeier et al, 2022;Park et al, 2019) 12), is characterized by increased expression of CX3CR1 (Supplementary Figure 13). The graded expression of CX3CR1 correlates with the differentiation of both CD4 and CD8 T cells towards an effector state (Zwijnenburg et al, 2023).…”
Section: Gene Expressionsupporting
confidence: 90%
“…Immunohistochemical results of AIH liver specimens confirm a significant accumulation of IL‐26 spatially distributed in liver portal areas and lesions of interface hepatitis. Studies have revealed the multiple cellular sources of IL‐26, including T cells, natural killer (NK) cells, NKp30 + γδT cells, CD68 + macrophages and, more recently, lung mucosal‐associated invariant T (MAIT) cells 31,33,34 . In our study, in situ confocal staining speculated that CD4 + T cells, CD8 + T cells and CD68 + macrophages in AIH represent hepatic reservoirs of IL‐26.…”
Section: Discussionmentioning
confidence: 71%
“…Studies have revealed the multiple cellular sources of IL-26, including T cells, natural killer (NK) cells, NKp30 + γδT cells, CD68 + macrophages and, more recently, lung mucosalassociated invariant T (MAIT) cells. 31,33,34 Th cell subsets. 10 Increased circulating soluble PD-1 levels, alongside with the frequency of PD-1 + CD8 + T cells, are positively associated with liver pathological markers in AIH.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of Th1 and Th2 cytokines secretion also indicated that cellular immunity was activated, clearing pathogenic bacteria and protecting organs from infection. IL-12 has been shown to promote cytotoxicity of pulmonary mucosal-associated invariant T cells and improve clearance of pathogenic bacteria by mucosal immunity ( 57 ). Overall, high survival rates are generally associated with better tissue protection.…”
Section: Discussionmentioning
confidence: 99%